Isofraxidin biosynthesis in Chloranthus: genomic insights into metabolic evolution of an early angiosperm phytoalexin - Liu, Yingying; Chen, Lu; Li, Ping; Wei, Shugen; Huang, Yuan; Tan, Mengjin; Wei, Ying; Peng, Feng; Pan, Yu; Song, Lisha; Wan, Lingyun; Yan, Zhigang; et al. (Frontiers in Plant Science, 2026)
As an early-diverging angiosperm lineage, Chloranthaceae produces specialized coumarins with documented antimicrobial and anti-inflammatory activities, which contribute to its ecological success. Isofraxidin, the most representative simple coumarin in this clade, exhibits significant pharmaceutical potential. However, its biosynthetic basis remains uncharacterized. Here, we assembled a high-quality triploid genome of Chloranthus spicatus (8.57 Gb, contig N50 = 8.76 Mb) to explore the evolution of defensive metabolism. Genomic analysis revealed an ancient whole-genome duplication event and expanded gene families associated with pathogen resistance. Metabolomic analysis identified at least 49 coumarin compounds in Chloranthus plants, significantly exceeding previous records. Integrated omics revealed 267 candidate biosynthetic genes across 9 enzyme families governing isofraxidin biosynthesis. Building on the upstream synthesis of the phenylpropanoid backbone, this study identifies amplified coumarin synthase (COSY) genes linked to umbelliferone accumulation, and specific CYP450s and O-methyltransferases catalyzing final structural modifications. This work elucidates the evolution of chemical defenses in early angiosperms and enables the engineering of plant-derived antimicrobials.